Copper(II) complexes of picolinamide incorporating both tricyanomethanido and 2-(aminomethyl)pyridine moieties. Issue 23 (2nd December 2017) - Wikaira, Jan L.; Bruda, Sandra; Landee, Christopher P.; Turnbull, Mark M.
Abstract: Reaction of picolinamide (pca) with potassium tricyanomethanide (tcm) and copper(II) perchlorate in 1-propanol gave [Cu(pca)2 (tcm)2 ] (1a and1b ) while addition of 2-(aminomethyl)pyridine (2-ampy) provided [Cu(pca)(2-ampy)(tcm)](ClO4 ) (2 ). These compounds have been characterized by IR, powder X-ray diffraction, single crystal X-ray diffraction, combustion analysis, and temperature-dependent magnetic susceptibility. Compound1a crystallized in the monoclinic space group C2/c whereas1b and2 crystallized in the triclinic space group P ī . In1a, the copper complexes stack alternately with semi-coordinated tcm ions creating layers, further stabilized by hydrogen bonding to neighboring layers. In1b, the tcm ions are coordinated to complete the octahedral coordination sphere around the copper ions and form staggered layers parallel to the ab face diagonal. In2, stacks of copper complexes form bilayers, held together by hydrogen bonding between tcm ions and amino groups, parallel to the a axis. Variable temperature magnetic susceptibility data were collected on1 and2 from 1.8–310 K. The data were fit to the Curie–Weiss law which showed no significant magnetic exchange as expected based upon the crystal structures [1  − Curie constant = 0.419(2) emu-K/mol-Oe, θ  = −0.10(6)°;2 – Curie constant = 0.438(1) emu-K/mol-Oe, θ  = 0.05(3)°]. Abstract :